Calculus of propositions in Bertrand rassell's logic - Naseef, Nebal (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research tries to concentrate on an essential and important issue in symbolic logic, which is the calculus of propositions in Rassell's logic. By studying this issue we will be able to understand propositions in Rassell's logic and its relationship with facts because of the great relationship between them. also we are going to know his opinion of Aristote's Categorical proposition. This research aims to study the issue of simple truth functions which are treated by calculus of propositions and deals with it as axiomatic and clarify the difference between material implication and formal implication. Finally it studies the axiomatic in calculus of propositions depending on the book principles of mathematics.